Subcellular localization of celery mannitol dehydrogenase. A cytosolic metabolic enzyme in nuclei. - Yamamoto, Y T (1997)
Mannitol dehydrogenase (MTD) is the first enzyme in mannitol catabolism in celery (Apium graveolens L. var dulce [Mill] Pers. cv Florida 638). Mannitol is an important photoassimilate, as well as providing plants with resistance to salt and osmotic stress. Previous work has shown that expression of the celery Mtd gene is regulated by many factors, such as hexose sugars, salt and osmotic stress, and salicylic acid. Furthermore, MTD is present in cells of sink organs, phloem cells, and mannitol-grown suspension cultures. Immunogold localization and biochemical analyses presented here demonstrate that celery MTD is localized in the cytosol and nuclei. Although the cellular density of MTD varies among different cell types, densities of nuclear and cytosolic MTD in a given cell are approximately equal. Biochemical analyses of nuclear extracts from mannitol-grown cultured cells confirmed that the nuclear-localized MTD is enzymatically active. The function(s) of nuclear-localized MTD is unknown.